Heparin induced thrombocytopenia: review. Issue 4 (August 2013) - Dasararaju, Radhika; Singh, Nirupama; Mehta, Amitkumar
Heparin induced thrombocytopenia (HIT) is a serious, potentially life and limb threatening immune adverse reaction to heparin. IgG antibodies against platelet factor 4 and heparin multimer complexes activate platelets to create a prothrombotic state. ELISA based immunoassay to detect these antibodies is sensitive while serotonin release assay is highly specific but is not widely available. 4T score is a simple score to calculate pre-test probability of HIT. Score <3 is highly specific to exclude the diagnosis. Alternate anticoagulants like lepirudin, argatroban or danaparoid are recommended in therapeutic dose to treat or prevent thrombotic events in HIT. Increased awareness of this condition among clinicians is important to ensure its early recognition and treatment to avoid serious complications.